The Friends Association for the Soviet Union in Chile 1927-1943 [a Associação de Amigos Da União Soviética No Chile 1927-1943] [la Asociación de Amigos de la Unión Soviética en Chile, 1927-1943] - Loyola-Tapia, M (Editora da P U C R S, 2016)
Using official archives and printed sources, this paper investigates the Friends Association for the Soviet Union, a communist organization that was founded in Chile during the first half of the 20th century. Considering the Russian Revolution of 1917 and the development of the Soviet Union as milestones in the construction of the identity and image of the Chilean communist militancy, the approach proposed here analyzes how Soviet ideas were present in the internal politics during that period. © 2016, Editora da P U C R S. All rights reserved.